2016
DOI: 10.1111/gcb.13283
|View full text |Cite
|
Sign up to set email alerts
|

Estimating indices of range shifts in birds using dynamic models when detection is imperfect

Abstract: There is intense interest in basic and applied ecology about the effect of global change on current and future species distributions. Projections based on widely used static modeling methods implicitly assume that species are in equilibrium with the environment and that detection during surveys is perfect. We used multiseason correlated detection occupancy models, which avoid these assumptions, to relate climate data to distributional shifts of Louisiana Waterthrush in the North American Breeding Bird Survey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 60 publications
(129 reference statements)
1
47
0
Order By: Relevance
“…Our results correlating initial occupancy with environmental covariates are, broadly speaking, consistent with biological expectation and a raft of previous studies that have indicated a significant relationship between species distributions and habitat (Robinson, Wilson, & Crick, ; Thogmartin, Sauer, & Knutson, ), climate (Barbet‐Massin & Jetz, ; Bellard, Bertelsmeier, Leadley, Thuiller, & Courchamp, ), or both (Seoane, Bustamante, & Díaz‐Delgado, ; Sohl, ). However, we suggest that estimated relationships between spatial variation in environmental covariates and colonization and extinction rates are of greater ecological interest than relatively phenomenological species distribution models or climate envelope models (Clement et al, ). The estimated vital rates of colonization and extinction bring us closer to understanding the dynamic process underlying the distribution of these species.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our results correlating initial occupancy with environmental covariates are, broadly speaking, consistent with biological expectation and a raft of previous studies that have indicated a significant relationship between species distributions and habitat (Robinson, Wilson, & Crick, ; Thogmartin, Sauer, & Knutson, ), climate (Barbet‐Massin & Jetz, ; Bellard, Bertelsmeier, Leadley, Thuiller, & Courchamp, ), or both (Seoane, Bustamante, & Díaz‐Delgado, ; Sohl, ). However, we suggest that estimated relationships between spatial variation in environmental covariates and colonization and extinction rates are of greater ecological interest than relatively phenomenological species distribution models or climate envelope models (Clement et al, ). The estimated vital rates of colonization and extinction bring us closer to understanding the dynamic process underlying the distribution of these species.…”
Section: Discussionmentioning
confidence: 84%
“…We used correlated‐detection models because the BBS generates spatially replicated surveys, and failure to account for spatial correlation of replicates can bias occupancy estimates (Hines et al, ). Finally, we used a finite mixture model to account for detection heterogeneity because of the variation in habitat and focal species abundance across the study area (Clement et al, ). A finite mixture model approximates the heterogeneity of detection probabilities by positing that the population consists of a mixture of routes which have either a relatively high detection probability or a relatively low detection probability.…”
Section: Methodsmentioning
confidence: 99%
“…Another relevant property of community occupancy models is that they allow occupancy probability to be obtained in relation to environmental covariates and to analyze climate change effects (Clement et al, ). Our results show that a higher percentage of forest cover reduces slightly the mean occupancy of bird communities.…”
Section: Discussionmentioning
confidence: 99%
“…Occupancy models provide estimates of occurrence probability for species that are corrected for imperfect detection (Bailey, MacKenzie, & Nichols, ; MacKenzie et al, ). These models enable us to rigorously evaluate the effects of environmental variables on occupancy probability, mapping species range dynamics (Kéry, Guillera‐Arroita, & Lahoz‐Monfort, ; Santika, McAlpine, Lunney, Wilson, & Rhodes, ), study the interactions between species (Michel, Jiménez‐Franco, Naef‐Daenzer, & Grüebler, ; Yackulic et al, ) and evaluate the effects of climate change (Clement, Hines, Nichols, Pardieck, & Ziolkowski, ). Multispecies occupancy models are a more complex framework, aimed at estimating total community richness (Dorazio & Royle, ; Dorazio, Royle, Söderström, & Glimskär, ; Kéry & Royle, ) and few studies have evaluated the effects of different habitats (Zipkin, DeWan, & Royle, ) and range shift over two different periods (Moritz et al, ; Tingley & Beissinger, ).…”
Section: Introductionmentioning
confidence: 99%
“…We modelled population‐specific local colonization and extinction along elevational gradients using dynamic (multi‐season) occupancy models (MacKenzie, Nichols, Hines, Knutson, & Franklin, ). This model is an appropriate and robust tool because it accounts for imperfect detection by camera traps (MacKenzie et al, ; Royle & Dorazio, ) and makes few assumptions about equilibrium or pseudo‐equilibrium (Clement, Hines, Nichols, Pardieck, & Ziolkowski, ). The dynamic occupancy modelling approach has a similar sampling scheme as Pollock’s robust design for mark‐recapture studies (Pollock, ).…”
Section: Methodsmentioning
confidence: 99%